Explaining Victim Impact from Cyber Abuse: An Exploratory Mixed Methods Analysis. Issue 10 (3rd October 2022) - Vakhitova, Zarina I.; Alston-Knox, Clair L.; Reeves, Ellen; Mawby, Rob I.
ABSTRACT: Crime and deviance can have a significant and long-lasting effect on victims. While the literature on victim impact from traditional types of crime like robbery or assault is well established, much smaller scholarship examines the impact of online forms of deviance with only a handful of studies focusing on the experiences of adult victims. The current paper analyses the data from a sample of the U.S. adults ( N = 746) using mixed methods to examine the perceived impact from different types of cyber abuse. A thematic analysis of open-ended responses identified five main types of victim impact: psychological, emotional, social, financial and positive. We also found that females, victims, who were abused by someone they knew, and who experienced multiple methods of abuse tended to experience higher impact. Besides, some methods of abuse appeared to affect victims more than others. Findings from this study contribute to our understanding of cyber abuse as a type of deviant behavior and help inform policy responses to the needs of cyber abuse victims.